2008
DOI: 10.1302/0301-620x.90b4.20497
|View full text |Cite
|
Sign up to set email alerts
|

Standardised consent forms on the website of the British Orthopaedic Association

Abstract: The British Orthopaedic Association has endorsed a website, www.orthoconsent.com, allowing surgeons free access to a bank of pre-written consent forms. These are designed to improve the level of information received by the patient and lessen the risk of successful litigation against surgeons and Health Trusts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 3 publications
0
38
0
1
Order By: Relevance
“…One method to improve these is to convey standardised information using procedure specific consent forms 19 . This approach has been reported to improve recall rates in patients undergoing knee arthroscopy and arthroplasty 20 .…”
Section: Discussionmentioning
confidence: 99%
“…One method to improve these is to convey standardised information using procedure specific consent forms 19 . This approach has been reported to improve recall rates in patients undergoing knee arthroscopy and arthroplasty 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Poor or incomplete documentation during the consent process denies the patient a full understanding of the procedure they are about to undergo, negatively impacting their decision making autonomy (13). This can also then subsequently expose hospitals and doctors to possible litigation (14), (15). Previous reviews of litigation relating to informed consent in the United States found errors in recording the risks of a procedure accounted for up to 70% of complaints alone (16).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-printed consent forms for common procedures in orthopaedic surgery have recently been supported by the British Orthopaedic Association 4. Use of pre-printed consent forms has not been widely incorporated into standard practice.…”
Section: Introductionmentioning
confidence: 99%